2010
DOI: 10.1007/s10653-010-9305-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive separation of phosphate oxyanion from aqueous solution using an inorganic adsorbent

Abstract: Phosphate removal from aqueous solution was explored using granular ferric hydroxide (GFH) as an inorganic adsorbent. Adsorption, desorption and kinetic studies were conducted on laboratory scale to evaluate the performance of GFH as an adsorbent for low concentrations of phosphate solution. The effect of pH on adsorption was investigated, and phosphate uptake was shown to decrease with an increase in solution pH, with maximum removal seen to occur at pH 3. The experimental data best fit the Temkin isotherm at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Adsorption of anion onto oxidic surface involves surface complexation phenomenon in the adsorption process. Previous studies (Namasivayam and Prathap, 2005;Saha et al, 2010) showed that the presence of oxidic adsorbents (e.g., hydroxylated mineral) plays an important role in the removal of anions from aqueous solutions. In this case, the adsorbent tantalum hydroxide is present in the following forms depending on the pH of the solution:…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption of anion onto oxidic surface involves surface complexation phenomenon in the adsorption process. Previous studies (Namasivayam and Prathap, 2005;Saha et al, 2010) showed that the presence of oxidic adsorbents (e.g., hydroxylated mineral) plays an important role in the removal of anions from aqueous solutions. In this case, the adsorbent tantalum hydroxide is present in the following forms depending on the pH of the solution:…”
Section: Resultsmentioning
confidence: 99%
“…Two models were used, with the results shown in Table 3. The Langmuir isotherm was applicable in cases where homogeneous adsorption occurred, with all adsorbed molecules having equal sorption activation energies [47,48].…”
Section: Phosphate Ion Adsorption Isotherms At Different Temperaturesmentioning
confidence: 99%
“…The Freundlich isotherm is used to describe systems of heterogeneous nature [50,51]. As the Freundlich equation is exponential, it assumes that as the adsorbate concentration increases, its concentration on the adsorbent surface increases as well [47]:…”
Section: Phosphate Ion Adsorption Isotherms At Different Temperaturesmentioning
confidence: 99%
“…27,28 Metal and metal-oxide adsorbents have high adsorption capacity and fast adsorption speed for phosphate, but they are easy to agglomerate, and excessive accumulation of most metals will cause toxicity. 29,30 Therefore, in contrast, the application of solid waste adsorption materials based on biochar can also alleviate the environmental pollution problem on the premise of ensuring the adsorption capacity and not producing secondary pollution, thus killing two birds with one stone. 11−14 Biochar modification by Ca is also promising as this method does not generate any toxic waste or byproducts and is easy to accomplish.…”
Section: Introductionmentioning
confidence: 99%